Hippocampal Connectivity of the Presubiculum in the Common Marmoset (Callithrix jacchus) - Honda, Yoshiko; Shimokawa, Tetsuya; Matsuda, Seiji; Kobayashi, Yasushi; Moriya-Ito, Keiko (Frontiers in Neural Circuits, 2022)
The marmoset (a New World monkey) has recently received much attention as an experimental animal model; however, little is known about the connectivity of limbic regions, including cortical and hippocampal memory circuits, in the marmoset. Here, we investigated the neuronal connectivity of the marmoset, especially focusing on the connectivity between the hippocampal formation and the presubiculum, using retrograde and anterograde tracers (cholera toxin-B subunit and biotin dextran amine). We demonstrated the presence of a direct projection from the CA1 pyramidal cell layer to the deep layers of the presubiculum in the marmoset, which was previously identified in the rabbit brain, but not in the rat. We also found that the cells of origin of the subiculo-presubicular projections were localized in the middle part along the superficial-to-deep axis of the pyramidal cell layer of the distal subiculum in the marmoset, which was similar to that in both rats and rabbits. Our results suggest that, compared to the rat and rabbit brains, connections between the hippocampal formation and presubiculum are highly organized and characteristic in the marmoset brain.